Dieta w życiu ascetycznym Ojców pustyni - Filipowski, Mateusz (Studia Theologica Varsaviensia, 2018)
The Diet in the ascetic life of Desert Fathers - Summary The author discusses in his article the diet practiced in the hermit environment of the Egyptian monks, in the period which is especially known to us from the conserved monastic sources, that is, the 4th and 5th centuries, in particular of the Apophthegmata Patrum and writings of Evagrius Ponticus. First, the author of the article outlines an ascetic perspective in the life and the environment of: St. Anthony the Hermit, St. Pachomius and the hermits of the settlements in Nitria, Kellia and Scetis. Then, he discusses in details elements of the hermit diet. Finally, he presents the theological and moral premises of their fasting practices.